SISTEM KONTROL UNTUK PERTANIAN BERBASIS INTERNET OF THINGS - Rafael Saktiaji Prakoso; Joni Fat; Endah Setyaningsih; Hugeng (TESLA: Jurnal Teknik Elektro, 2022)
The fuzzy logic method is a method that is not much different from the case that resembles the level of thinking of people's logical reasoning. It has two inputs from two different sensors with linguistic values or called membership degrees and the resulting voltage is 0 - 5.5 Volts. The PIR sensor will work optimally at a distance of 4 meters where for the sensitivity of the PIR sensor itself it can react in a time range of 3-4 seconds and for its own range of approximately 4 meters and on the LM35 sensor test that this sensor is better for temperature due to the sensitivity of detecting temperature when compared to a thermometer, this sensor will be able to stabilize the room temperature which is less precise, so that in making the room for automatic cooling the sensor works optimally in a room measuring 4 x 4 meters.